A Criminal Psychological Approach to Immigration Resilience - Ákos, Erdélyi; Barbara, Mágó (Magyar Rendészet, 2025)
Introduction: Managing migration is one of the biggest challenges of the 21st century, in the public, social, political, economic and legal spheres. Research on the psychological effects of migration is a highly complex phenomenon, but scholars have mostly focused on the psychology of immigration, looking at psychological processes only from the perspective of the migrants themselves. Aims: This study seeks to find a link between the lack of resilience of admissions and the criminality of immigrants, by examining the transpersonal dimensions of the psychology of migration. Methods: The authors explore the social conditions for successful integration and the deviant behaviours that may be associated with failure to integrate by analysing the intersection of migration and criminal psychology. They also attempt to adapt the concept of resilience to the factors of migration in order to achieve the research objectives. Results: Immigration, settlement and ultimately citizenship acquisition of people from different cultures requires a high degree of resilience from all private and public actors involved in migration. Effective integration is a guarantee of peace, security and prosperity, while lack of integration tends towards criminalisation. Conclusions: The key to successful integration is the ability to adapt to changing circumstances through multiple actors.